In vitro Study of Bedaquiline Resistance in Mycobacterium tuberculosis Multi-Drug Resistant Clinical Isolates - Degiacomi, Giulia; Sammartino, José Camilla; Sinigiani, Virginia; Marra, Paola; Urbani, Alice; Pasca, Maria Rosalia (Frontiers in Microbiology, 2020)
Tuberculosis (TB) is one of the major causes of deaths related to antimicrobial resistance worldwide because of the spread of Mycobacterium tuberculosis multidrug resistant (MDR and XDR) clinical isolates. To fight MDR and XDR tuberculosis, three new antitubercular drugs, bedaquiline (BDQ), delamanid, and pretomanid were approved for their use in clinical setting. Unfortunately, BDQ quickly acquired two main mechanisms of resistance, consisting in the mutations in both atpE gene, encoding the target, and in Rv0678, coding for the repressor of MmpS5-MmpL5 efflux pump. To better understand the spreading of BDQ resistance in MDR- and XDR- TB, in vitro studies could be a valuable tool. To this aim, in this work an in vitro generation of M. tuberculosis mutants resistant to BDQ was performed starting from two MDR clinical isolates as parental cultures. The two M. tuberculosis MDR clinical isolates were firstly characterized by whole genome sequencing, finding the main mutations responsible for their MDR phenotype. Furthermore, several M. tuberculosis BDQ resistant mutants were isolated by both MDR strains, harboring mutations in both atpE and Rv0678 genes. These BDQ resistant mutants were further characterized by studying their growth rate that could be related to their spreading in clinical settings. Finally, we also constructed a data sheet including the mutations linked to BDQ resistance that could be useful for the early detection of BDQ-resistance in MDR/XDR patients with the purpose of a better management of antibiotic resistance in clinical settings.